An Analysis of Nancy’s Character Images in "Oliver Twist" - Wang, Yincheng (Journal of Theory and Practice of Contemporary Education, 2023)
"Oliver Twist" is a realistic literary work created by the famous British writer Dickens, in which the image of Nancy is the most commendable. In addition to the distinctive character characteristics, the author's observation and reflection on British capitalist society implied by Nancy's characters has also become an important factor in the popularity of the novel in the world and becoming a classic of the generation. Nancy's fragile, kind, and cowardly personality traits are a true portrayal of the millions of ordinary people in British capitalist exploitation, and also the final lament of ordinary people when they are unable to resist capitalist exploitation. By analyzing the image of Nancy, we can more clearly observe the real environment of British society during the post industrial revolution period of the 19th century, and more accurately criticize the exploitative society in Britain.